Analysis of the Development Trend in Forensic Odontology Based on CiteSpace - Ma, Hao-Tian; Xiong, Hua-Ye; Lu, Ye; Li, Bing; Lai, Jiang-Hua (Fa yi xue za zhi, 2023)
To realize the dynamic visualization of forensic odontology based on the bibliometrics methods, and capture the research hotspots and identify the future development trend. Literature articles published from January 1995 to December 2020 were searched according to specific subject words in the core data set of Web of Science. The visualization analysis of publishing country, institution, discipline, author, co-cited journal and keywords was performed by CiteSpace 5.7.R5W software. The annual analysis of publications showed an upward trend of forensic odontology research literature year by year, with the number of annual publications more than 110 in the last five years. Developed countries were the main source of contributions and the average centrality was greater than 0.2. The research of forensic odontology involved multiple disciplines, including stomatology, biology, computer science and medical imaging, with a distinct interdisciplinary feature. A total of 115 nodes were obtained by keyword cluster analysis. The principal line of forensic odontology mainly included individual identification and age estimation and the emergence of hotspots was closely related to new technologies. Population-based odontology investigation, improvement of traditional dental age estimation method and dental age estimation based on new technology were popular research in forensic odontology. Developing countries urgently need to increase the focus on related research. It may be an important direction for the development of forensic odontology to establish and enrich the regional dental database, develop new odontology identification technology combined with frontier and high-end technology, and develop the identification program based on advanced information technology.